Caloric restriction and the adipokine leptin alter the SDF-1 signaling axis in bone marrow and in bone marrow derived mesenchymal stem cells. (15th July 2015) - Periyasamy-Thandavan, Sudharsan; Herberg, Samuel; Arounleut, Phonepasong; Upadhyay, Sunil; Dukes, Amy; Davis, Colleen; Johnson, Maribeth; McGee-Lawrence, Meghan; Hamrick, Mark W.; Isales, Carlos M.; Hill, William D.
Highlights: Caloric restriction induces CXCR4 mediated migration. CR may induce leptin sensitivity. Enhanced bone formation was observed in CR mice treated with leptin. Density of marrow adipocytes was greatly enhanced by long-term CR. Abstract: Growing evidence suggests that the chemokine stromal cell-derived factor-1 (SDF-1) is essential in regulating bone marrow (BM) derived mesenchymal stromal/stem cell (BMSC) survival, and differentiation to either a pro-osteogenic or pro-adipogenic fate. This study investigates the effects of caloric restriction (CR) and leptin on the SDF-1/CXCR4 axis in bone and BM tissues in the context of age-associated bone loss. For in vivo studies, we collected bone, BM cells and BM interstitial fluid from 12 and 20 month-old C57Bl6 mice fed ad-libitum (AL), and 20-month-old mice on long-term CR with, or without, intraperitoneal injection of leptin for 10 days (10 mg/kg). To mimic conditions of CR in vitro, 18 month murine BMSCs were treated with (1) control (Ctrl) : normal proliferation medium, (2) nutrient restriction (NR) : low glucose, low serum medium, or (3) NR + leptin : NR medium + 100 ng/ml leptin for 6–48 h. In BMSCs both protein and mRNA expression of SDF-1 and CXCR4 were increased by CR and CR + leptin. In contrast, the alternate SDF-1 receptor CXCR7 was decreased, suggesting a nutrient signaling mediated change in SDF-1 axis signaling in BMSCs. However, in bone SDF-1, CXCR4 and 7 gene expression increase with age and this is reversed with CR, while addition of leptin returns this to the "aged" level. Histologically bone formation was lower in the calorically restricted mice and BM adipogenesis increased, both effects were reversed with the 10 day leptin treatment. This suggests that in bone CR and leptin alter the nutrient signaling pathways in different ways to affect the local action of the osteogenic cytokine SDF-1. Studies focusing on the molecular interaction between nutrient signaling by CR, leptin and SDF-1 axis may help to address age-related musculoskeletal changes.